Investigation of wired and wireless services based on OFDM DSB-RC transmission in the presence of modulation chirp of a DEMZM - Almeida, Paulo (2013)
In this paper, we investigate the performance of intensity modulation with optical carrier reduced by biasing a dual-electrode Mach-Zehnder modulator (DEMZM) below its quadrature point, in the presence of controlled modulation chirp. The effects of the modulation chirp and of the bias point of a DEMZM on the received signal are analytically derived for small-signal operation. The interaction of these two effects is assessed in terms of optical signal to noise ratio (OSNR) required for a BER = 10(-9), through a comparison between double sideband (DSB) modulation and double sideband - reduced carrier (DSB-RC) modulation, by numerical simulation. We found that the power of the optical carrier has impact on the optimum value of the α chirp parameter and that a positive value of the α chirp parameter can be the optimum value to drive a DEMZM, depending on the central frequency of the orthogonal frequency division multiplexing (OFDM) signal and on the DEMZM bias point.